Exploring Listening Relationship Pattern of Information Approval Process in Science Learning: A Qualitative Investigation Using TBLA (Transcript Based Lesson Analysis) - Maya Umi Hajar; Dedy Dwi Putra (PAEDAGOGIA, 2024)
This study reveals listening relationship patterns in the information approval process used to improve the quality of learning dialogue, especially in science learning. A qualitative method with a case study approach was used to analyze listening relationship patterns in science learning during one semester. A total of 3 science teachers, 31 students, and two academics involved in lesson study for learning communities were selected to capture a mutual listening relationship pattern in receiving information with a natural performance and not tense when observing. Observation, documentation, and clinical interviews were used as data collection techniques. Video and audio recorders were involved as documentation tools for this study. Transcript-based lesson analysis (TBLA) was included in conducting data analysis. The listening relationship patterns analysis results in classical discussion sessions in cycles 1–3, which tend to have semi-equal listening relationship patterns. Meanwhile, the listening relationship pattern in group discussion sessions in cycles 1 to 3 tends to be the isolated listening relationship group pattern. The shift in the pattern of listening relationships in group discussion sessions is caused by several factors, including student collaboration awareness, heterogeneous composition of students, tasks, and questions that challenge students, and appropriate interruptions of teacher direction. The research results provide a reference for reflection on developing teacher professionalism to improve more effective and meaningful learning.